Effect of trace niobium on the microstructure and properties of full-pearlite steel used in the high-strength hypereutectoid wire rods - Xiaokun Pan; Jincheng Li; Chaolei Zhang; Xinping Mao; Wenjun Wang; Shuize Wang; Guilin Wu; Junheng Gao; Honghui Wu; Haitao Zhao (Journal of Materials Research and Technology)
The present study investigated the impact of 20–80 ppm Nb on the microstructure and properties of hypereutectoid pearlite steel. Remarkably, even trace amounts of Nb exhibited a favorable effect on the refinement of austenite grain. The addition of the Nb element resulted in a reduction of pearlite transition temperature, leading to a decrease of approximately 13% in lamellar spacing and 11% in the size of pearlite colonies. Furthermore, the dragging effect of the Nb element on the carbon atoms in hypereutectoid steel facilitated the control and refinement of network carbides. These findings offer valuable theoretical guidance for the production of ultra-high-strength wire rods. When the Nb content reached 80 ppm, it promoted the precipitation of (Ti, V)C, while simultaneously improving the morphology of square carbides. The grain refining strengthening mechanism accounted for about 70% of the overall strengthening effect observed in high carbon wire rods, with the influence of the Nb element primarily targeting grain refinement. Consequently, the incorporation of minute quantities of Nb presents a promising avenue for the development of ultra-high-strength hypereutectoid wire rods, offering significant potential for enhancing their strength properties.